Abnormal Synergetic Effect of Organic and Halide Ions on the Stability and Optoelectronic Properties of a Mixed Perovskite via In Situ Characterizations. Issue 28 (23rd May 2018) - Long, Mingzhu; Zhang, Tiankai; Liu, Mingzhen; Chen, Zefeng; Wang, Chen; Xie, Weiguang; Xie, Fangyan; Chen, Jian; Li, Gang; Xu, Jianbin
Abstract: The mixed cation lead mixed halide perovskite (MLMP) Cs x FA1‐ x PbI y Br3‐ y is one of the most promising candidates for both single‐junction and tandem solar cells due to its high efficiency and remarkable stability. However, the composition effect on thermal stability and photovoltaic performances has not yet been comprehensively investigated. Therefore, the interplay between composition, crystal structure, morphology, and optoelectronic properties under heat stress, is systematically elucidated here through a series of in situ characterizations. It is revealed for the first time that the FA + and Br − release synchronously at first even under mild annealing. This leads to a serious FA‐ and Br‐deficiency issue, with only 88.3% of Br and 90.2% of FA retained after annealing at 100 °C, which significantly magnifies the hysteresis, phase segregation, and instability issues. Finally, a trace amount of FA + and Br − is introduced onto the post‐annealed MLMP surface to compensate for the deficiency through vacancy filling. The degradation lifetime to 80% of the initial efficiency ( t 80 ) is improved from 504 to 1056 h and the hysteresis issue is also well resolved. This work highlights the importance of the synergetic composition effect of the organic cation and halide anion on stability and efficiency optimization for long‐term applications. Abstract : The synergetic composition effect of an organic cation and halide anion on the stability and optoelectronic properties of Cs x FA1‐ x PbI y Br3‐ y, is systematically investigated through a series of in situ characterizations. FA and Br ions release synchronously at first even under 100 °C annealing, leading to composition deficiency, hysteresis, and instability issues. With a trap‐filling strategy, the thermal stability, photostability, and performance are remarkably enhanced.